Mitochondrial metabolism regulation and epigenetics in hypoxia - Laird, Madison; Ku, Jennifer C.; Raiten, Jacob; Sriram, Sashwat; Moore, Megan; Li, Yong (Frontiers in Physiology, 2024)
The complex and dynamic interaction between cellular energy control and gene expression modulation is shown by the intersection between mitochondrial metabolism and epigenetics in hypoxic environments. Poor oxygen delivery to tissues, or hypoxia, is a basic physiological stressor that sets off a series of reactions in cells to adapt and endure oxygen-starved environments. Often called the "powerhouse of the cell," mitochondria are essential to cellular metabolism, especially regarding producing energy through oxidative phosphorylation. The cellular response to hypoxia entails a change in mitochondrial metabolism to improve survival, including epigenetic modifications that control gene expression without altering the underlying genome. By altering the expression of genes involved in angiogenesis, cell survival, and metabolism, these epigenetic modifications help cells adapt to hypoxia. The sophisticated interplay between mitochondrial metabolism and epigenetics in hypoxia is highlighted by several important points, which have been summarized in the current article. Deciphering the relationship between mitochondrial metabolism and epigenetics during hypoxia is essential to understanding the molecular processes that regulate cellular adaptation to reduced oxygen concentrations.